A prospective observational study on understanding of idiopathic generalized epilepsies namely juvenile myoclonic epilepsy and epilepsy with generalized tonic-clonic seizure alone by electroencephalogram with updated terminology in a tertiary care hospital - Jannat Ara, Kazi; Rizvi, Abu Nasir; Barman, Kanuj Kumar; Sobhan, Khair M. (International Journal of Research in Medical Sciences, 2022)
Background: In 2017, the international league against epilepsy (ILAE) classification of epilepsies described the “genetic generalized epilepsies”, which contained the “idiopathic generalized epilepsies”. This study delineates the four syndromes comprising the IGEs: childhood absence epilepsy, juvenile absence epilepsy, juvenile myoclonic epilepsy (JME), and epilepsy with generalized tonic-clonic seizures alone (GTCA). JME patients usually present with myoclonic seizures, and GTCA patients present with GTCS only after awakening from sleep. Aim of the study was to identify the differences between juvenile myoclonic epilepsy and epilepsy with generalized tonic-clonic seizures alone by semiology and EEG with updated terminology under the observation of the clinicians. Methods: This was a prospective observational study and was conducted in the epilepsy clinic, department of neurology, Bangabandhu Sheikh Mujib medical university, from February 2021 to July 2022. The sample size was 60. Results: Among 60 patients, family history was present in 12 (20%) and 6 (10%) JME and GTCA patients, respectively. In this study, the EEG finding of generalized spike-wave (2.5-5.5 Hz) was seen in 26 (43%) and 19 (32%) among JME and GTCA patients, respectively. Generalized Polyspike wave (2.5-5.5 Hz) was seen in 26 (43%) JME patients, and EEG was normal in 15 out of 60 patients of epilepsy. In EEG findings, 2.5-5.5 Hz generalized spike-wave should be diagnosed in JME and GTCA patients as a special group of IGEs. Conclusions: In this study, we have recognized and differentiated between juvenile myoclonic epilepsy and generalized tonic-clonic seizures alone by semiology and EEG in IGE syndromes as a special grouping among the IGEs is helpful as they carry prognostic and therapeutic implications.